PERAN KEMAMPUAN MANAJERIAL TERHADAP MANAJEMEN LABA DANBIAYA MODAL EKUITAS SEBAGAI MEKANISME DALAM MENINGKATKAN NILAI PERUSAHAAN - Obertus Bilang La'bi; Suwandi Ng; Lukman Lukman (Magister Akuntansi, Universitas Atma Jaya Makassar, 2018)
The aims of this study was to investigate the effect of managrial ability on earnings management and cost of equity capital, to investigate the effect of earnings management, cost of equity capital, and managerial ability on firm value, and to investigate the effect of managerial ability on firm value mediated by earnings management and cost of equity capital. Population used is the whole company public listed in Indonesia Stock Exchange period 2015-2017. Number of samples are 125 firms each year, was selected by purposive sampling method and using secondary data, i.e. the annual report and financial statements. The analytical method used is path analysis and hypothesis mediation analysed by using Sobel test. The results of this research show that managerial ability has a negatiive and significant impact on earnings management and cost of equity capital. While earnings management and cost of equity capital has a negative significant influence on firms value, managerial ability has a positive and significant influence on firms value. This study also shows that earnings management plays a role in mediating managerial ability on firms value, while cost of equity capital do not play a role in mediating managerial ability on firm values. The implication of this research is that managers must improve their managerial ability so that they can reduce earnings management practices and manage the cost of equity capital to increase the firm value. Companies that are able to reduce discretionary accruals and cost of equity capital will make investor to invest.